Elaboração e validação de questionário sobre o conhecimento da Doença Pulmonar Obstrutiva Crônica entre profissionais da atenção primária - Erikson Custódio Alcântara; Krislainy de Sousa Corrêa; Marcelo Fouad Rabahi (UniEVANGÉLICA, 2018)
Objective: To develop and validate a questionnaire to assess awareness of Chronic Obstructive Pulmonary Disease in primary care professionals. Methods: Methodological study with primary care professionals. It developed the questionnaire using the Likert scale. After semantic validation was applied on two occasions with an interval of 15 to 20 days. We evaluated the reproducibility by Kappa and reliability by Cronbach's alpha. Results: The construction of the questionnaire included different topics of Chronic Obstructive Pulmonary Disease prevention, diagnosis, treatment and monitoring distributed in 16 items. After phrase and semantic validation adjustments we applied the questionnaire in 89 professionals from primary health care, three items passed phrase reconstruction before being applied to present 57.14% of disagreement between the judges. The questionnaire presented reliability with Cronbach α = 0.763 and reproducibility on most items (87.5%) of good to excellent (Kappa: 0.61 to 0.88). Conclusion: The questionnaire has met the psychometric properties and was reliable and reproducible evaluation of knowledge of Chronic Obstructive Pulmonary Disease among primary care professionals